Crucible for growing gallium oxide crystals and preparation method thereof

By using aluminum, scalp and sand, and magnesium sand, the problem of high existing high cost and poor performance is solved, and the low cost and efficient production of oxide crystal growth is achieved.

CN116874285BActive Publication Date: 2025-01-28BEIJING GACHUANG TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310761208.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-26
Publication Date
2025-01-28
Estimated Expiration
2043-06-26

Smart Images

  • Figure CN116874285B_ABST
    Figure CN116874285B_ABST
Patent Text Reader

Abstract

The present invention provides a crucible for growing gallium oxide crystals and a preparation method thereof. The crucible is made of raw materials including aluminum oxide, zircon sand and magnesia sand; wherein the mass ratio of aluminum oxide, zircon sand and magnesia sand is (1-3):(2-4):(3-5), and the refractoriness of the crucible is ≥1900°C. The present invention adopts an iridium-free technical route, which can not only avoid high-temperature oxidation of the crucible and chemical reaction with the melt, but also reduce the use of precious metal iridium by using an oxide crucible instead of an iridium gold crucible, making the gallium oxide growth process not only simpler and more controllable, but also lower in cost, and has greater industrialization prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of semiconductor material preparation, and in particular to a crucible for growing gallium oxide crystals and a preparation method thereof. Background Art

[0002] The bandgap width of gallium oxide semiconductor is about 4.9eV, and the breakdown electric field strength is as high as 8MV / cm, which is much higher than semiconductor materials such as silicon, silicon carbide and gallium nitride. The larger the bandgap width, the higher the device can withstand voltage and temperature, and the greater the output power of the device. At the same time, the larger the bandgap width, the higher the chemical stability of the device, which enables the power device to work in a more severe environment, greatly improving the stability and reliability of the system. In addition, the theoretical loss of gallium oxide is 1 / 6 of silicon carbide and 1 / 3 of gallium nitride, that is, the loss is reduced by 86% on the basis of SiC's 86% loss reduction compared to Si. Because of its superior physical properties, high thermal and chemical stability, low energy loss, good controllability and low cost, it has shown great potential in the manufacture of high-voltage, high-temperature, high-power electronic devices, solar-blind ultraviolet optoelectronic devices, and ultraviolet transparent conductive electrodes.

[0003] The choice of crucible material is determined by the crystal being grown and its properties in the molten state. The crucible is in direct contact with the growing crystal and its melt, and has an important influence on the heat transfer characteristics of the crystal growth process. Therefore, the choice of crucible material is one of the control factors for whether the crystal growth process can be achieved and the quality of the crystal structure. Gallium oxide materials have a high melting point (about 1800°C). At present, the crucible material for growing gallium oxide crystals is mainly iridium metal, which can be grown at 1800°C and in a certain oxygen atmosphere. However, iridium metal is expensive, more than three times the price of gold, and the cost is high. From the perspective of large-scale production, it is difficult to expand the number of equipment to increase production capacity, and iridium metal relies on imports, and the supply chain has great risks.

[0004] The contents of the background technology section are merely the technologies known to the inventors and do not necessarily represent the prior art in the field. Summary of the invention

[0005] In order to solve the problems of high temperature oxidation and crucible cost during the growth of gallium oxide crystals, the present invention provides a crucible for growing gallium oxide crystals and a preparation method thereof.

[0006] The crucible for growing gallium oxide crystals provided by the present invention is made of raw materials including aluminum oxide, zircon sand and magnesium sand;

[0007] Wherein, the mass ratio of the alumina, the zircon sand and the magnesia sand is (1-3):(2-4):(3-5), and the refractoriness of the crucible is ≥1900°C.

[0008] In some embodiments of the present invention, the crucible has a thermal conductivity of 7.0 to 8.0 at a temperature of 1000 to 1800°C and a linear expansion coefficient of 9.0 to 9.5×10 -6 / ℃, heat capacity is 700~800J / kg·K, volume density is 3.8~4.2g / cm 3 .

[0009] In some embodiments of the present invention, the room temperature compressive strength of the crucible is 60-65 MPa, 0.1 MPa, the load softening temperature is greater than 1700° C., and the linear change rate is -0.5-1.6%.

[0010] In some embodiments of the present invention, the crucible is fired at a temperature of 1750-1850°C.

[0011] The present invention provides a method for preparing a crucible for growing gallium oxide crystals, comprising:

[0012] Mixing zircon sand and magnesia sand uniformly to obtain a mixture;

[0013] reacting the ultrafine aluminum oxide powder with the mixture to obtain a reactant;

[0014] The reactants are mixed evenly with fillers and auxiliary materials, and then poured into a mold for compression molding to obtain a blank;

[0015] The blank is sequentially cured, calcined and cooled to obtain the crucible;

[0016] Wherein, the mass ratio of the ultrafine alumina powder, the zirconium sand and the magnesia sand is (1-3):(2-4):(3-5), and the refractoriness of the crucible is ≥1900°C.

[0017] In some embodiments of the present invention, the curing temperature is 150-160° C., and the curing time is 3-4 hours.

[0018] In some embodiments of the present invention, the calcination temperature is 1750-1850° C., and the calcination time is 2-3 hours.

[0019] In some embodiments of the present invention, the particle size of the ultrafine alumina powder is 5 to 10 microns, and the particle size of the zircon sand and the magnesia sand is 100 to 200 microns.

[0020] In some embodiments of the present invention, the zircon sand and the magnesia sand are mixed uniformly to obtain the mixture, which comprises:

[0021] The zircon sand and the magnesia sand are sequentially added into a high-speed mixer, and stirred at a speed of 800 to 1000 r / min for 45 to 60 minutes to obtain the mixture.

[0022] In some embodiments of the present invention, the ultrafine aluminum oxide powder and the mixture are reacted to obtain the reactant, which comprises:

[0023] The ultrafine aluminum oxide powder and the mixture are reacted at a temperature of 250 to 300° C. for 50 to 60 minutes to obtain the reactant.

[0024] The present invention adopts an iridium-free technical route, which can not only avoid high-temperature oxidation of the crucible and chemical reaction with the melt, but also reduce the use of precious metal iridium by using an oxide crucible instead of an iridium-gold crucible, making the gallium oxide growth process not only simpler and more controllable, but also lower in cost, and has greater industrial prospects.

[0025] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The accompanying drawings constituting a part of the present disclosure are used to provide a further understanding of the present disclosure. The illustrative embodiments of the present disclosure and their descriptions are used to explain the present disclosure and do not constitute improper limitations on the present disclosure.

[0027] Figure 1 A process flow chart for preparing a crucible according to an embodiment of the present invention. DETAILED DESCRIPTION

[0028] In the following, only some exemplary embodiments are briefly described. As those skilled in the art will appreciate, the described embodiments may be modified in various ways without departing from the spirit or scope of the present invention. Therefore, the drawings and descriptions are considered to be exemplary and non-restrictive in nature.

[0029] The disclosure below provides many different embodiments or examples for implementing the present invention. In order to simplify the disclosure of the present invention, the components and settings of specific examples are described below. Of course, they are only examples, and the purpose is not to limit the present invention. In addition, the present invention can repeat reference numbers and / or reference letters in different examples, and this repetition is for the purpose of simplicity and clarity, which itself does not indicate the relationship between the various embodiments and / or settings discussed. In addition, the present invention provides various specific examples of processes and materials, but those of ordinary skill in the art can appreciate the application of other processes and / or the use of other materials.

[0030] In addition, unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as those generally understood by those of ordinary skill in the art to which the present invention belongs. It will also be understood that terms, such as those defined in commonly used dictionaries, should be interpreted as having a meaning consistent with their meaning in the context of the relevant technology and the present invention, and will not be interpreted in an idealized or overly formal sense unless explicitly defined in this article.

[0031] As used herein, "about" or "approximately" includes the stated value and means within an acceptable range of deviation from the particular value as determined by one skilled in the art, taking into account the measurement in question and the errors associated with the measurement of the particular quantity (i.e., the limitations of the measurement system). For example, "about" can mean within one or more standard deviations, or within ±30%, ±20%, ±10%, or ±5% of the stated value.

[0032] The following is a more detailed description of the specific embodiments of the present invention in conjunction with the accompanying drawings and examples, so that the scheme of the present invention and its advantages in various aspects can be better understood. However, the specific embodiments and examples described below are only for the purpose of illustration, rather than for limiting the present invention.

[0033] The thermal conductivity of gallium oxide crystals at 1000-1800°C is about 12.0, and the linear expansion coefficient is about 9.5×10 -6 / ℃, liquid state is about 720J / kg·K (solid state heat capacity is about 560J / kg·K), volume density is about 5.8g / cm 3 The melting point is about 1800°C. The crucibles currently used to prepare gallium oxide crystals are basically iridium crucibles. The thermal conductivity of iridium metal at a temperature of 1000-1800°C is about 147.0, and the linear expansion coefficient is about 6.5×10 -6 / ℃, heat capacity is about 130J / kg·K, volume density is about 22.6g / cm 3 , with a melting point of about 2450°C. As mentioned earlier, the cost of iridium crucibles is very high, and it is difficult to mass produce, and the supply chain has great risks. In addition, the thermal conductivity of iridium metal is too strong, which is not conducive to crystal growth, and its chemical stability is average.

[0034] The main raw materials of the crucible provided by the present invention are aluminum oxide, zircon sand and magnesia sand, wherein the mass ratio of aluminum oxide, zircon sand and magnesia sand is about (1-3):(2-4):(3-5). The refractoriness of the crucible provided by the present invention can be greater than or equal to 1900°C, the thermal stability is good, and it hardly reacts chemically with gallium oxide, which is very beneficial to the growth of crystals. The present invention adopts an iridium-free technical route, which can not only avoid high-temperature oxidation of the crucible and chemical reaction with the melt, but also reduce the use of precious metal iridium by using an oxide crucible instead of an iridium gold crucible, making the gallium oxide growth process not only simpler and more controllable, but also lower in cost (the comprehensive cost is about 1 / 100 of the current cost of an iridium crucible), and has greater industrial prospects.

[0035] In some embodiments of the present invention, the crucible has a thermal conductivity of about 7.0 to 8.0 at a temperature of 1000 to 1800°C, and a linear expansion coefficient of about 9.0 to 9.5×10 -6 / ℃, heat capacity is about 700~800J / kg·K, and volume density is about 3.8~4.2g / cm 3 , the melting point is about 1900-2000℃. The thermal expansion coefficient of the crucible is slightly smaller than that of the gallium oxide crystal, so that no large compressive stress is formed on the crystal during the growth of the gallium oxide crystal, thereby improving the growth quality of the gallium oxide crystal. The crucible has a thermal conductivity that matches the gallium oxide crystal, which is beneficial for heating the melt in the heating zone and cooling the crystal in the cooling zone. Whether it is thermal conductivity, linear expansion coefficient or heat capacity, it is very close to gallium oxide, which is very beneficial for high-quality control of gallium oxide crystal growth. The heat capacity of the crucible provided by the present invention is 5 times that of metal iridium, and it has good thermal insulation properties. It can reduce heat dissipation during long-term crystal growth and improve thermal efficiency, thereby achieving the purpose of saving energy.

[0036] In some embodiments of the present invention, the compressive strength of the crucible at room temperature is about 60-65 MPa, the softening temperature under load of 0.1 MPa is greater than 1700°C, and the linear change rate is about -0.5-1.6%. The crucible has a high melting point and high temperature strength, has high chemical stability, can still maintain sufficient strength at the crystal growth temperature, and will not decompose and oxidize in a high temperature oxygen atmosphere, and basically does not react chemically with the crystal or melt.

[0037] Figure 1 A method for preparing the above-mentioned crucible provided by an embodiment of the present invention is shown, comprising the following steps S10 to S40.

[0038] S10: Mix the zircon sand and the magnesia sand uniformly to obtain a mixture.

[0039] Optionally, the particle size of the zircon sand and the magnesia sand is 100 to 200 microns.

[0040] In some embodiments of the present invention, this step may be: adding zircon sand and magnesia sand into a high-speed mixer in sequence, stirring at a speed of 800 to 1000 r / min for 45 to 60 minutes to obtain a mixture.

[0041] S20: reacting the ultrafine aluminum oxide powder and the mixture to obtain a reactant.

[0042] The mass ratio of alumina, zircon sand and magnesia sand is approximately (1-3):(2-4):(3-5).

[0043] Optionally, the particle size of the ultrafine alumina powder is 5 to 10 microns. The combination of the ultrafine alumina powder of 5 to 10 microns and the zircon sand and magnesia sand of 100 to 200 microns can make the crucible have a high density, thereby improving the heat resistance and high temperature strength of the crucible.

[0044] In some embodiments of the present invention, this step includes: reacting the ultrafine alumina powder and the mixture at a temperature of 250 to 300° C. for 50 to 60 minutes to obtain a reactant.

[0045] S30: The reactants are mixed evenly with the fillers and auxiliary materials, and then poured into a mold for compression molding to obtain a blank.

[0046] Optionally, the filler is kaolin and the auxiliary material is clay.

[0047] Optionally, the pressure during compression molding is 10 to 30 MPa.

[0048] S40: curing, calcining and cooling the blank in sequence.

[0049] In some embodiments of the present invention, the curing temperature is 150-160° C., and the curing time is 3-4 hours.

[0050] In some embodiments of the present invention, the calcination temperature is 1750-1850° C., and the calcination time is 2-3 hours.

[0051] After cooling to room temperature, the oxidation-resistant and high-temperature-resistant crucible of the present invention is obtained.

[0052] The preparation method provided by the invention is simple, and the prepared crucible has excellent performance and low cost.

[0053] The present invention is described below with reference to specific embodiments. The process condition values ​​taken in the following embodiments are all exemplary, and the possible value ranges are as shown in the above invention content. For process parameters not specifically noted, conventional techniques can be used. The detection methods used in the following embodiments are all conventional detection methods in the industry. Unless otherwise specified, the reagents and instruments used in the technical solutions provided by the present invention can be purchased from conventional channels or the market.

[0054] Example 1

[0055] This embodiment prepares a crucible for growing gallium oxide crystals, and the specific process is as follows:

[0056] 20 parts of zircon sand and 50 parts of magnesia sand were added into a high-speed mixer in sequence at a stirring speed of about 1000 r / min for about 45 min to obtain a mixture.

[0057] The mixture and 25 parts of ultrafine aluminum oxide powder were fed into a reaction kettle, the reaction temperature was about 250° C., the reaction time was about 60 min, and a reactant was obtained.

[0058] The reactants, 3 parts of kaolin and 2 parts of clay are poured into a crucible mold and pressed into shape by a press at a pressure of about 15 MPa. The formed crucible is placed in a curing room for curing at a temperature of about 150°C for about 3 hours, and then placed in a high-temperature calcining furnace for drying and calcining at a temperature of about 1750°C for about 3 hours, and then cooled to obtain the product.

[0059] The average particle size of the ultrafine alumina powder is about 5 microns, and the average particle sizes of the zircon sand and the magnesia sand are about 100 microns and 120 microns respectively.

[0060] The performance indicators of the crucible are shown in Table 1. The prepared crucible was used to grow gallium oxide crystals at a growth rate of about 10 mm / h.

[0061] Example 2

[0062] This embodiment prepares a crucible for growing gallium oxide crystals, and the specific process is as follows:

[0063] 30 parts of zircon sand and 50 parts of magnesia sand were added into a high-speed mixer in sequence at a stirring speed of about 800 r / min for about 60 min to obtain a mixture.

[0064] The mixture and 15 parts of ultrafine aluminum oxide powder were fed into a reactor, the reaction temperature was about 300° C., the reaction time was about 55 min, and a reactant was obtained.

[0065] The reactants, 3 parts of kaolin and 2 parts of clay are poured into a crucible mold and pressed into shape by a press at a pressure of about 20 MPa. The formed crucible is placed in a curing room for curing at a temperature of about 160°C for about 3 hours, and then placed in a high-temperature calcining furnace for drying and calcining at a temperature of about 1850°C for about 2.5 hours, and then cooled to obtain the product.

[0066] The average particle size of the ultrafine alumina powder is about 10 microns, and the average particle sizes of the zircon sand and the magnesia sand are about 150 microns and 140 microns respectively.

[0067] The performance indicators of the crucible are shown in Table 1. The prepared crucible was used to grow gallium oxide crystals at a growth rate of about 15 mm / h.

[0068] Example 3

[0069] This embodiment prepares a crucible for growing gallium oxide crystals, and the specific process is as follows:

[0070] 30 parts of zircon sand and 40 parts of magnesia sand were added into a high-speed mixer in sequence at a stirring speed of about 900 r / min for about 50 min to obtain a mixture.

[0071] The mixture and 25 parts of ultrafine aluminum oxide powder were fed into a reaction kettle, the reaction temperature was about 270° C., the reaction time was about 50 min, and a reactant was obtained.

[0072] The reactants, 3 parts of kaolin and 2 parts of clay are poured into a crucible mold and pressed into shape by a press at a pressure of about 30 MPa. The formed crucible is placed in a curing room for curing at a temperature of about 155°C for about 3.5 hours, and then placed in a high-temperature calcining furnace for drying and calcining at a temperature of about 1800°C for about 2.2 hours, and then cooled to obtain the product.

[0073] The average particle size of the ultrafine alumina powder is about 13 microns, and the average particle sizes of the zircon sand and magnesia sand are about 180 microns and 190 microns, respectively.

[0074] The performance indicators of the crucible are shown in Table 1. The prepared crucible was used to grow gallium oxide crystals at a growth rate of about 10 mm / h.

[0075] Comparative Example 1

[0076] This comparative example prepares a crucible for growing gallium oxide crystals, and the specific process is as follows:

[0077] 95 parts of zirconium dioxide, 3 parts of kaolin and 2 parts of clay are poured into a crucible mold and pressed into shape by a press at a pressure of about 15MPa. The formed crucible is placed in a curing room for curing at a temperature of about 150°C for about 3 hours, and then placed in a high-temperature calcining furnace for drying and calcining at a temperature of about 1750°C for about 3 hours, and then cooled to obtain the product.

[0078] The average particle size of zirconium dioxide is about 150 microns.

[0079] The performance indicators of the crucible are shown in Table 1. The prepared crucible was used to grow gallium oxide crystals, and it was found that a reaction layer with a thickness of nearly 2 mm would grow on the surface of the crucible, and as the heating progressed, the crucible would soften significantly, resulting in the inability to grow gallium oxide crystals normally afterwards.

[0080] Comparative Example 2

[0081] This comparative example prepares a crucible for growing gallium oxide crystals, and the specific process is as follows:

[0082] 95 parts of magnesium oxide, 3 parts of kaolin and 2 parts of clay are poured into a crucible mold and pressed into shape by a press at a pressure of about 20 MPa. The formed crucible is placed in a curing room for curing at a temperature of about 150°C for about 3 hours, and then placed in a high-temperature calcining furnace for drying and calcining at a temperature of about 1750°C for about 3 hours, and then cooled to obtain the crucible.

[0083] The average particle size of magnesium oxide is about 180 microns.

[0084] The performance indicators of the crucible are shown in Table 1. The prepared crucible was used to grow gallium oxide crystals, and it was found that the quality of the prepared crystals was poor and the crystal yield was very low.

[0085] Comparative Example 3

[0086] This comparative example prepares a crucible for growing gallium oxide crystals, and the specific process is as follows:

[0087] 45 parts of zircon sand and 50 parts of magnesia sand were added into a high-speed mixer in sequence at a stirring speed of about 900 r / min for about 50 min to obtain a mixture.

[0088] The mixture, 3 parts of kaolin and 2 parts of clay are poured into a crucible mold and pressed into shape by a press at a pressure of about 30 MPa. The formed crucible is placed in a curing room for curing at a temperature of about 155°C for about 3.5 hours, and then placed in a high-temperature calcining furnace for drying and calcining at a temperature of about 1800°C for about 2.2 hours, and then cooled to obtain the crucible.

[0089] The average particle sizes of zircon sand and magnesia sand are about 180 microns and 190 microns respectively.

[0090] The performance indicators of the crucible are shown in Table 1. The prepared crucible was used to grow gallium oxide crystals, and it was found that a reaction layer with a thickness of nearly 1 mm would grow on the surface of the crucible, and as the heating progressed, the crucible would soften to a certain extent, resulting in the inability to grow gallium oxide crystals normally afterwards.

[0091] Comparative Example 4

[0092] This comparative example prepares a crucible for growing gallium oxide crystals, and the specific process is as follows:

[0093] 50 parts of zircon sand and 45 parts of ultrafine alumina powder were fed into a reactor, the reaction temperature was about 270° C., the reaction time was about 50 min, and a reactant was obtained.

[0094] The reactants, 3 parts of kaolin and 2 parts of clay are poured into a crucible mold and pressed into shape by a press at a pressure of about 30 MPa. The formed crucible is placed in a curing room for curing at a temperature of about 155°C for about 3.5 hours, and then placed in a high-temperature calcining furnace for drying and calcining at a temperature of about 1800°C for about 2.2 hours, and then cooled to obtain the product.

[0095] The average particle size of the ultrafine alumina powder is about 13 microns, and the average particle size of the zircon sand is about 180 microns.

[0096] The performance indicators of the crucible are shown in Table 1. The prepared crucible was used to grow gallium oxide crystals, and it was found that a reaction layer with a thickness of nearly 1.5 mm would grow on the surface of the crucible, and as the heating progressed, the crucible would soften to a certain extent, resulting in the inability to grow gallium oxide crystals normally afterwards.

[0097] Comparative Example 5

[0098] This comparative example prepares a crucible for growing gallium oxide crystals, and the specific process is as follows:

[0099] 50 parts of magnesia and 45 parts of ultrafine alumina powder were fed into a reactor, the reaction temperature was about 270° C., the reaction time was about 50 min, and a reactant was obtained.

[0100] The reactants, 3 parts of kaolin and 2 parts of clay are poured into a crucible mold and pressed into shape by a press at a pressure of about 30 MPa. The formed crucible is placed in a curing room for curing at a temperature of about 155°C for about 3.5 hours, and then placed in a high-temperature calcining furnace for drying and calcining at a temperature of about 1800°C for about 2.2 hours, and then cooled to obtain the product.

[0101] The average particle size of the ultrafine alumina powder is about 13 microns, and the average particle size of the magnesia is about 190 microns.

[0102] The performance indicators of the crucible are shown in Table 1. The prepared crucible was used to grow gallium oxide crystals, and it was found that the quality of the prepared crystals was poor and the crystal yield was low.

[0103] Comparative Example 6

[0104] The only difference between this comparative example and Example 3 is that the calcination temperature is 1500°C.

[0105] The performance indicators of the crucible are shown in Table 1. The prepared crucible was used to grow gallium oxide crystals, and it was found that the quality of the prepared crystals was poor.

[0106] Comparative Example 7

[0107] The only difference between this comparative example and Example 3 is that the calcination temperature is 1950°C.

[0108] The performance indicators of the crucible are shown in Table 1. The prepared crucible was used to grow gallium oxide crystals, and it was found that a reaction layer with a thickness of nearly 1 mm would grow on the surface of the crucible, and as the heating progressed, the crucible would soften to a certain extent, resulting in the inability to grow gallium oxide crystals normally afterwards.

[0109] Table 1

[0110]

[0111]

[0112] From Comparative Example 1, it can be seen that when high-melting-point zirconium dioxide is directly used as the crucible material to grow gallium oxide crystals at 1800°C, zirconium dioxide will chemically react with the gallium oxide melt (the thickness of the reaction layer is close to 2 mm), and the crucible will soften significantly, so gallium oxide crystals cannot be grown normally.

[0113] From Comparative Example 2, it can be seen that when the crucible is made directly of magnesium oxide with a high melting point, since the expansion coefficient of magnesium oxide material is larger than that of gallium oxide, when the gallium oxide crystals are cooled, solidified and crystallized, the crucible will give the growing gallium oxide crystals a certain compressive stress, thereby increasing the defects of the crystals, reducing the quality of the crystals, and even destroying the growth of the crystals.

[0114] From Comparative Example 3, it can be seen that the crucible made of zircon sand and magnesia sand still reacts to a certain extent with the gallium oxide melt (the thickness of the reaction layer exceeds 1 mm), and the crucible softens to a certain extent, so gallium oxide crystals cannot grow normally.

[0115] From Comparative Example 4, it can be seen that the crucible made of zircon sand and alumina still reacts to a certain extent with the gallium oxide melt (the thickness of the reaction layer exceeds 1.5 mm), and the crucible softens to a certain extent, so gallium oxide crystals cannot grow normally.

[0116] From Comparative Example 5, it can be seen that although the crucible made of magnesia and alumina does not react with the gallium oxide melt, the expansion coefficient of the crucible is larger than that of gallium oxide. Therefore, when the gallium oxide crystals solidify and crystallize, the crucible will give the growing gallium oxide crystals a certain compressive stress, thereby increasing the defects of the crystals, and thus high-quality gallium oxide crystals cannot be grown normally.

[0117] From Comparative Example 6, it can be seen that when the calcination temperature is lower than 1750°C, the expansion coefficient of the obtained crucible is larger than that of gallium oxide. Therefore, when gallium oxide solidifies and crystallizes, the crystal will be subjected to compressive stress, which increases growth defects and reduces the quality of crystal growth.

[0118] It can be seen from Comparative Example 7 that when the calcination temperature is higher than 1850°C, zircon sand and magnesia sand will undergo an obvious chemical reaction, and the magnesium content in the crucible will be reduced, and lower than the magnesium content in Example 3. Therefore, the prepared crucible will still react with the gallium oxide melt to a certain extent (the thickness of the reaction layer exceeds 1 mm), and the crucible will soften to a certain extent, so gallium oxide crystals cannot be grown normally.

[0119] The crucible provided by the invention has low cost and is very suitable for growing gallium oxide crystals.

[0120] Obviously, the above embodiments are merely examples for clearly explaining the present invention, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the protection scope of the present invention.

Claims

1. A method for preparing a crucible for growing gallium oxide crystals, characterized in that: include: Mixing zircon sand and magnesia sand uniformly to obtain a mixture; reacting the ultrafine aluminum oxide powder with the mixture to obtain a reactant; The reactant is mixed evenly with a filler and an auxiliary material, and then poured into a mold for compression molding to obtain a blank, wherein the filler is kaolin and the auxiliary material is clay; The blank is sequentially cured, calcined and cooled to obtain the crucible; Wherein, the mass ratio of the ultrafine alumina powder, the zirconium sand and the magnesia sand is (1-3): (2-4): (3-5), and the refractoriness of the crucible is ≥ 1900°C; The particle size of the ultrafine alumina powder is 5-10 microns, and the particle size of the zircon sand and the magnesia sand is 100-200 microns; The calcination temperature is 1750~1850℃, and the calcination time is 2~3h.

2. The preparation method according to claim 1, characterized in that: The curing temperature is 150~160℃ and the curing time is 3~4h.

3. The preparation method according to claim 1, characterized in that: The zircon sand and the magnesia sand are mixed evenly to obtain a mixture comprising: The zircon sand and the magnesia sand are sequentially added into a high-speed mixer, and stirred at a speed of 800-1000 r / min for 45-60 min to obtain the mixture.

4. The preparation method according to claim 1, characterized in that: The ultrafine aluminum oxide powder and the mixture are reacted to obtain reactants including: The ultrafine alumina powder and the mixture are reacted at a temperature of 250-300° C. for 50-60 minutes to obtain the reactant.

5. A crucible for growing gallium oxide crystals, characterized in that: It is prepared by the preparation method described in any one of claims 1 to 4.

6. The crucible according to claim 5, characterized in that The crucible has a thermal conductivity of 7.0-8.0 at a temperature of 1000-1800°C and a linear expansion coefficient of 9.0-9.5×10 -6 / ℃, heat capacity is 700~800J / kg·K, and volume density is 3.8~4.2g / cm 3 .

7. The crucible according to claim 5, characterized in that The room temperature compressive strength of the crucible is 60-65 MPa, the softening temperature under load of 0.1 MPa is greater than 1700° C., and the linear change rate is -0.5-1.6%.

Citation Information

Patent Citations

  • Preparation of oxide single crystal

    JP2000313697A

  • Gallium oxide single crystal and method for producing the same

    JP2011190127A